2015
DOI: 10.1523/jneurosci.3161-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms for Integrating Prior Knowledge and Likelihood in Value-Based Probabilistic Inference

Abstract: In Bayesian decision theory, knowledge about the probabilities of possible outcomes is captured by a prior distribution and a likelihood function. The prior reflects past knowledge and the likelihood summarizes current sensory information. The two combined (integrated) form a posterior distribution that allows estimation of the probability of different possible outcomes. In this study, we investigated the neural mechanisms underlying Bayesian integration using a novel lottery decision task in which both prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 65 publications
2
32
0
Order By: Relevance
“…In games where reinforcement learning has been used to model behavior, animal (48,49), and human (8) subjects often display success-stay/fail-switch strategy similar to those observed in our experiments. Our task differs from typical reinforcement learning tasks in that it requires weighing sensory evidence and choice options where the latter have no explicit value or probability associated with them (50). Nonetheless, humans may perform the task by assigning value to choice options (51) or by treating successful trials as rewards.…”
Section: Discussionmentioning
confidence: 99%
“…In games where reinforcement learning has been used to model behavior, animal (48,49), and human (8) subjects often display success-stay/fail-switch strategy similar to those observed in our experiments. Our task differs from typical reinforcement learning tasks in that it requires weighing sensory evidence and choice options where the latter have no explicit value or probability associated with them (50). Nonetheless, humans may perform the task by assigning value to choice options (51) or by treating successful trials as rewards.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the neural representation involved in the integration of these 2 sets of information. Ting et al 49. investigated the neural mechanisms underlying Bayesian integration using a decision-making task in which participants were required to estimate the reward probability by combining past experience (prior knowledge) with current sensory information (likelihood), and showed that the mPFC plays a role in this Bayesian integration.…”
Section: Discussionmentioning
confidence: 99%
“…They found that multivoxel pattern of activity in OFC represents the log posterior probability distribution on latent causes. In our previous study (Ting et al, 2015), we found that mPFC correlated with the mean of the posterior distribution on probability of reward. The present study adds to this literature by showing that mPFC represents the subjective weight necessary for the integration of prior and likelihood information when these two sources of information were presented.…”
Section: Neural Computations For Subjective Weightmentioning
confidence: 66%
“…In cognitive neuroscience, there is a growing interest in studying the neurocomputational substrates involved in a variety of inference tasks, from how people use cue reliability as prior information to guide perceptual decision making (Forstmann, Brown, Dutilh, Neumann, & Wagenmakers, 2010;Mulder, Wagenmakers, Ratcliff, Boekel, & Forstmann, 2012), make financial decisions based on prior information about partner's reputation (Fouragnan et al, 2013), combine prior and likelihood information about reward probability (d 'Acremont, Schultz, & Bossaerts, 2013;Ting, Yu, Maloney, & Wu, 2015), to infer latent causes (Chan, Niv, & Norman, 2016) and other people's intentions (Chambon et al, 2017). These studies pointed to the role of medial prefrontal cortex (mPFC) and orbitofrontal cortex (OFC) in inference, from representing prior information (Forstmann et al, 2010;Fouragnan et al, 2013;Ting et al, 2015;Vilares, Howard, Fernandes, Gottfried, & Kording, 2012), current observation or sensory evidence (d' Acremont et al, 2013;Ting et al, 2015) to the combination of prior and current information (Chambon et al, 2017;Chan et al, 2016;Ting et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation